Immunogenicity and safety of an investigational quadrivalent meningococcal conjugate vaccine administered as a booster dose in children vaccinated against meningococcal disease 3 years earlier as toddlers: A Phase III, open-label, multi-center study. Issue 1 (31st January 2022) - Piazza, Franco M.; Virta, Miia; Paassilta, Marita; Ukkonen, Benita; Ahonen, Anitta; Esteves-Jaramillo, Alejandra; Forsten, Aino; Seppa, Ilkka; Ding, Jian; Neveu, David; Jordanov, Emilia; Dhingra, Mandeep S.
ABSTRACT: Booster doses of meningococcal conjugate vaccines induce long-term protection against invasive meningococcal disease. We evaluated the immunogenicity and safety of a booster dose of MenACYW-TT in pre-school children who were primed 3 years earlier with MenACYW-TT or MCV4-TT (Nimenrix®). In this Phase III, open-label, multi-center study (NCT03476135), children (4–5 years old), who received a primary dose of MenACYW-TT or MCV4-TT as toddlers in a previous study, received a booster dose of MenACYW-TT. Titers of antibody against meningococcal serogroups A, C, W and Y were measured by serum bactericidal assay using human (hSBA) and baby rabbit (rSBA) complement in samples collected before (D0) and 30 days after (D30) booster vaccination. Safety was assessed over the 30-day study period. Ninety-one participants received the booster dose. In both study groups, hSBA titers increased from D0 to D30; serogroup C titers [95% confidence interval] were higher in the MenACYW-TT-primed vs MCV4-TT-primed group at D0 (106 [73.2, 153] vs 11.7 [7.03, 19.4], respectively) and D30 (5894 [4325, 8031] vs 1592 [1165, 2174], respectively); rSBA results were similar. Nearly all participants achieved ≥1:8 hSBA and rSBA titers at D30, which were higher or comparable to those observed post-primary dose, suggesting rapid booster responses. At D0, all hSBA and rSBA titers were higher than those observed pre-primary dose, suggesting persistence of immunogenicity. The MenACYW-TT booster dose was well-tolerated and had similar safety outcomes across study groups. These findings suggest that MenACYW-TT elicits robust booster responses in children primed 3 years earlier with MenACYW-TT or MCV4-TT.